Coronary aneurysm and stent fracture following stenting of a myocardial bridge. Issue 1 (3rd November 2015) - Lu, Hao; Ge, Lei; Ge, Junbo
Abstract : Myocardial bridge is the most common congenital coronary anomaly. We represent an extremely rare case of stent fracture combination with coronary aneurysm following stenting of a myocardial bridge. This 60‐years‐old male patient underwent coronary angiography in the local hospital four years ago. Coronary angiography revealed a myocardial bridge in the distal left anterior descending coronary artery (LAD). A 3.0 mm × 29 mm sirolimus eluting stent was deployed in the distal LAD. Three years later, repeat coronary angiography showed a large coronary aneurysm in the mid segment of the stent. The patient subsequently underwent coronary artery bypass grafting with left internal mammary artery (LIMA) to the distal segment of the LAD. But six months later, another coronary angiography showed a stent fracture in mid portion of the stent associated with a large coronary aneurysm, and the LIMA graft was totally occluded. A possible mechanism of stent fracture was long‐standing and cyclic mechanical stress on the stent by myocardium. These forces over a period of time may lead to metal fatigue and eventually fracture. Based on the observation of fracture and aneurysm in this study, we recommend that myocardial bridge should not be treated with intracoronary stenting. © 2015 Wiley Periodicals, Inc.